BOOK REVIEW A Rule Book for Arguments, 5th edition Anthony Weston Hackett Publishing ISBN 13-978-1-62466-654-4 - Barnes, John (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
The title should be read in an academic context i.e. not everyday squabble. The book is a slim at just 102 pages and is meant for use as a desk reference to assist students and faculty to check the logic developed or presented to them in a thesis or dissertation.